Disaster Risk Reduction in Rural Indonesia: Evaluation of the Japan Red Cross Program in Pujiharjo Village - Adisa, Meyralda Dara; Widodo, Pujo; Kurniadi, Anwar; Wilopo, Wilopo (Preventia: The Indonesian Journal of Public Health, 2025)
Pujiharjo Village in Malang Regency, Indonesia, is highly vulnerable to natural disasters. In 2021, the Indonesian Red Cross (PMI) partnered with the Japanese Red Cross Society (JRCS) to implement a community-based disaster preparedness program. This study evaluates the program's effectiveness in terms of community participation, institutional support, and alignment with the Sendai Framework for Disaster Risk Reduction 2015–2030. Using a qualitative case study, data were collected through document analysis of Vulnerability and Capacity Assessments (VCA), Community Action Plans (CAP), and local SOPs. Thematic analysis explored disaster risk perception, governance, mitigation investment, and emergency preparedness. The program successfully improved risk awareness, formed disaster preparedness teams (SIBAT), and developed digital evacuation routes and risk maps. Planning documents such as SOPs and CAPs were established. However, SOP understanding remained low (64% unfamiliar), vulnerable group inclusion and cross-sectoral coordination were limited, early warning systems were absent, and post-disaster recovery planning was lacking.